The role of knowledge management in supply chains: evidence from the Italian food industry. (27th January 2010) - Corso, Mariano; Dogan, Seyhan Firdevs; Mogre, Riccardo; Perego, Alessandro
This study deals with interorganisational Knowledge Management (KM) in the Italian food industry. Based on case studies, the paper defines the need for knowledge sharing amongst supply chain members in different collaborative activities. Then a framework is presented for investigating how Information Technology (IT)-based solutions for Supply Chain Management (SCM) fulfil the KM needs of the firms. Finally, the knowledge sharing and management enabled by the IT-based solutions for SCM are evaluated in terms of supply chain performance.